Impact of UP Design Core membership on the development of competencies for professional practice - Vinasoy, Krichelle Joy A.; Quevedo, Ma. Teresa (Quezon City University of the Philippines Diliman, 2025)
Student organizations enhance learning by offering opportunities and fostering essential skills beyond the classroom. UP Design Core (UPDC), a student-run organization that primarily caters to interior design students, supports collaboration, relationship-building, and professional development through various projects and initiatives. This study investigates the perspectives of selected UP BS Interior Design alumni and former UPDC members on how their involvement in the organization complements formal academic learning in developing competencies essential to professional interior design practice. Using an exploratory qualitative approach, fifteen (15) participants were selected through purposive and snowball sampling. Data from semi-structured online interviews were analyzed using thematic analysis. Findings reveal that UPDC activities (workshops, field trips, events, and organizational work) and experiences (leadership roles, tambayan sessions, and peer-to-peer learning) enhanced soft skills including communication, teamwork, problem-solving, adaptability, leadership, professionalism, interpersonal relations, and time management. Hard skills developed included proficiency in computer software, graphic design, drafting and presentation techniques, digital literacy, business and office skills, interior photography and staging, material familiarity, and marketing and merchandising. These skills closely aligned with those identified by participants as essential to the professional practice of interior design. UPDC complemented formal academic learning through reinforcement of technical skills, industry exposure, improved communication and presentation abilities, peer-based learning, and strong support systems. It also fostered discipline, self-confidence, and a sense of responsibility. The study concludes that UPDC is a vital extension of classroom instruction, bridging education and professional readiness through meaningful, real-world experiences aligned with industry-relevant competencies.
In partial fulfillment for the Degree of Bachelor of Science in Interior Design
Thesis
Keywords: Interior decoration; Interior decoration -- Study and teaching (Higher) -- Philippines; Experiential learning -- Philippines; Professional education -- Philippines; Career development; skills -- Study and teaching -- Philippines; Student organization; UP Design Core